Eksplorasi Nilai Pendidikan Islam Awal Dalam Tradisi Lokal Sebagai Model Pendidikan Alternatif di Era Kontemporer - Ghozali Ghozali; Sugeng Listyo Prabowo (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
This study aims to explore the values ​​of early Islamic education reflected in the local religious study tradition and its relevance as an alternative educational model in the contemporary era. Early Islamic education has become a primary foundation for the formation of Muslim civilization and character, emphasizing the balance between knowledge, faith, and morals. The local religious study tradition in Indonesia is a legacy of classical Islamic education that maintains spiritual, moral, and social values ​​in community-based learning practices. This study uses a descriptive qualitative approach with a (library research) method that focuses on exploring the concepts, values, and relevance of early Islamic education as reflected in the local religious study tradition. Primary data were obtained from classical Islamic literature such as traditional books, works of previous scholars, and historical sources related to the early Islamic education system. Meanwhile, secondary data include research results, scientific journals, academic books, and contemporary writings relevant to the theme of local religious study and modern Islamic education. The results show that local religious study contains authentic Islamic values ​​such as sincerity, exemplary behavior, togetherness, and respect for knowledge. These values ​​not only reflect the spirit of classical Islamic education but are also relevant for application in contemporary education systems that tend to be rational and individualistic. The local religious study tradition has the potential to become a holistic alternative educational model because it integrates cognitive, affective, and spiritual aspects within a single learning process. Therefore, revitalizing early Islamic educational values ​​through the local religious study tradition can be a solution for shaping students' religious and social character amidst the challenges of modernization and globalization.